Modular composite hydrogels from cholesterol-functionalized polycarbonates for antimicrobial applications1. Issue 34 (14th September 2015) - Lee, Ashlynn L. Z.; Venkataraman, Shrinivas; Fox, Courtney H.; Coady, Daniel J.; Frank, Curtis W.; Hedrick, James L.; Yang, Yi Yan
<x xml:space="preserve">Abstract</x> A modular and versatile approach of mixing pre-optimized functional components with ABA-triblock gelators to access drug-loaded or antimicrobial gel is presented.